Cultivo de girassol na safrinha no Oeste do Paraná: efeitos do espaçamento entre linhas e populações de plantas - Orlando, Auri Francisco (2008)
In order to study the effects of changes in the spacing between row and the plant population in the agronomic performance of sunflowers, grown in second season in the western region of Paraná, led to an experiment in the field of Experimental C. Vale - Cooperative Agroindustrial in Palotina - PR. Was evaluated, the hybrid MG2 in design of blocks at random with split plots, using four spacings (E1 = 0.90 m, E2 = 0.75 m, E3 = 0.60 m and E4 = 0.45 m) and four population (P1 = 27,000, P2 = 35,000, P3 = 43,000 and P4 = 51,000 plants ha-1) with four replications. It was evaluated: plants height (AP) stem diameter (DC), leaves dry mass (MFS), dry mass stem + petiole (MSPC), dry mass chapter (MSCAP), leaf area (AF), chapter diameter (DCAP), grains mass per chapter (MGCAP), degree of filling of the chapter (GECPA), mass of a thousand grains (MMG), productivity (PROD), content of oil (TO) and production of oil (DB). There was only interaction between people in the variable spacing and AP. For variables, MSF; MSCP; MSCAP; MGCAP; AF and TO, no significant difference was observed according to the variation of the population of sunflower plants. As for variables: DC; PC; GEC; MMG; MGCAP; PROD DB and there was reduction of all these in row with population increase of sunflower plants. The change in spacing between rows to influence the culture in a meaningful way only the GECAP being the lowest values observed in populations of plants intermediate (0.60 and 0.75 m). However, the spacing between rows of sowing not proved a limiting factor and can be changed depending on the machinery available for the operations of sowing and harvesting, however must be avoided high densities of plants in any spacing.